Charles Richet. A Nobel Prize Winning Scientist’s Exploration of Psychic Phenomena by Carlos S. Alvarado - Evrard, Renaud (Journal of Scientific Exploration, 2020)
Carlos S. Alvarado is a well-known specialist of the history of parapsychology, and also famous for his pedagogical skills mostly as an affiliate of the Parapsychology Foundation and the Alvarado and Zingrone Institute for Research and Education. Most of the material used in this book was already available online on his blog (https://carlossalvarado.wordpress.com) as it is a collection of previously published essays. I’m part of the people who publicly endorsed the book because Alvarado is clearly one of the most qualified authors able to deal with this topic, but here I will provide a complementary expertise based on my reading of the book and my own work on the history of French parapsychology (Evrard, 2016). (I’m also contributed to the Appendix E “Bibliography about and by Charles Richet with emphasis on psychic phenomena”, 119-132). Charles Richet (1850-1935) is a French physiologist (Nobel laureate 1913) who had contributed to many fields, among them psychology and psychical research. The book gathers six essays while trying to exhaustively cover these specific contributions through various glasses: a general overview of his interest in psychic phenomena (Chap. 1, 1-26), a discussion of his metapsychic autobiography (Chap. 2, 27-44), an analysis of his early ideas on mental suggestion and his pioneering use of probabilities in human sciences (Chap. 3, 45-54), his various attempts to create gateways between psychology and psychical research (Chap. 4, 55-66), a review of his masterpiece The traité de métapsychique (Chap. 5, 67-84), and a final comment about his own conclusions about what he learnt from psychical research and the survivalist hypothesis (Chap. 6, 85-96). The first four appendices cover small historical points as Richet’s séances with famous medium Leonara Piper (97-102), one of his observation of moving ectoplasm (103-104), a note about the term “ectoplasm” which he didn’t coin (105-106), and an extract from his Traité (107-118) about the scientific statute of “metapsychics”, his own term for parapsychology, in which we have a nice illustration of his clever and Hugolian expression style.